Effect of Artificial Insemination on production performance of dairy cattle in Case of Sayo District West Wollega Zone, Ethiopia - Mohammed Yousuf (Research Horizon, 2022)
The study was conducted in Sayo district with the objective of assessing challenges and opportunities of artificial insemination on dairy cattle, to document potential opportunities of artificial insemination, to identify the challenges of artificial insemination and to assess the perception of farmers on the AI technology in the study area. Three kebeles, three were taken purposively and 20 households from each kebele were randomly selected. The data were collected using semi structured questionnaires, interview and direct observation. The reproductive and productive data were analysed statistical software (SAS version 9.3.1 where as other data were analysed by simple descriptive statistics. The result of this finding shows that the overall mean of daily milk and lactation length of dairy cows in the Sayo distinct were5.83+0.82L and 240+18.43 days respectively whereas the overall mean of age at first calving, calving interval and number of services in the study area were 968.42+269.83, 449+22.09 days and 1.93+0.71times respectively.